Nucleocytoplasmic transport in C9orf72-mediated ALS/FTD - Zhang, Ke (Nucleus, 2016)
A GGGGCC hexanucleotide repeat expansion in C9orf72 is the most common genetic cause of familial amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Recent studies indicate that disruption of nucleocytoplasmic transport pathways play a critical role in the pathogenesis of C9orf72-mediated ALS/FTD (C9-ALS). Here, we discuss mechanisms by which C9orf72 mutations cause nucleocytoplasmic transport deficits and contribute to disease pathogenesis. We review the current literature regarding nucleocytoplasmic transport disruption in C9-ALS, and discuss implications and directions for future research.